New TIPARP inhibitor rescues mitochondrial function and brain injury in ischemic stroke - Yang Cai; Hongfeng Gu; Lu Li; Xue Liu; Ying Bai; Ling Shen; Bing Han; Yungen Xu; Honghong Yao (Pharmacological Research)
Ischemic stroke is a high-mortality disease that urgently requires new therapeutic strategies. Insufficient cerebral blood supply can induce poly (ADP-ribose) polymerase (PARP) activation and mitochondrial dysfunction, leading to tissue damage and motor dysfunction. We demonstrate that the expression of TCDD inducible PARP (TIPARP) is elevated in ischemic stroke patients and mice. Knockdown of Tiparp reduces brain infarction and promotes recovery of motor function in ischemic stroke mice. A rationally designed TIPARP inhibitor, XG-04-B1, promotes repair of brain injury and recovery of motor function in ischemic stroke mice. Mechanistically, XG-04-B1 increases neuronal plasticity and inhibits astrocyte activation in ischemic stroke mice. In addition, eukaryotic translation initiation factor 3 subunit B (EIF3B) is a direct target of TIPARP. TIPARP interacts with EIF3B through nucleoplasmic redistribution, leading to mitochondrial dysfunction. Knockdown of Tiparp and inhibition of TIPARP via XG-04-B1 restore mitochondrial homeostasis in ischemic stroke mice. Taken together, TIPARP activation contributes to mitochondrial dysfunction and subsequent brain injury, and is therefore a promising therapeutic target for stroke.